Los algoritmos para el cálculo de la raíz cuadrada y sus antecedentes en textos escolares antiguos - Núñez i Espallargas, Josep M.; Servat Susagne, J. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
First of all, there is an analysis of the historical and scientifical motivations that lead to the inclusion of the usual square root algorithm in mathematics in elementary education, as well as of the textbook that introduced them for the first time in Spain. Secondly we take into account two alternative algorithms for the calculation of square roots proposed by modern didactical literature of mathematics teaching, and show that, in both cases, it is possible to find precedents of their utilization in old elementary textbooks.